الضغوط النفسية لعينة من معلمات التربية الخاصة بولاية الوادي - حميداني، صونيا, أحمودة، هدى (جامعة الوادي university of Eloued, 2022)
الملخص: هدف هذا البحث التعرف على الضغوط النفسية لدى مربيات التربية الخاصة بولاية الوادي حيث استخدمنا المنهج الوصفي الارتباطي، وبلغ عدد العينة إلى 30معلمة من معلمات التربية الخاصة تم اختيارهم بالطريقة العشوائية البسيطة. وتم استخدام الحزمة الإحصائية spssبغرض تحليل البيانات عن طريق الأساليب الإحصائية. وتمثله النتائج في الضغوط النفسية لدى مربيات التربية الخاصة تتسم بالانخفاض. ولا توجد فروق ذات دلالة إحصائية بين الضغوط النفسية لدى مربيات التربية الخاصة تبعا لمتغير العمر، ولا توجد فروق ذات دلالة إحصائية تبعا لمتغير المستوى التعليمي، ولا توجد فروق ذات دلالة إحصائية لمربيات التربية الخاصة ومتغير الدورات التدريبية. وفي الختام قمنا بتوصيات إجرائية أهمها مساعدة وتشجيع مربيات التربية الخاصة في الالتحاق في الدورات والدراسات العليا والتي أهمها في مجال عملهم، حيث الملاحظ ندرة هذه الدراسات وخاصة العليا، ومقترحات لبحوث المستقبل Abstract This research aims at recognizing the stress that special education teachers suffer in El Oued. In this work we used the descriptive correlative approach, taking a simple random sample of 30 special education female teachers. Spss "statistical package for social sciences" was used in order to analyze the data based on statistical methods. The results represents that the stress levels among special education teachers are low. There are no statistically significant differences between the levels of stress based on the variable of educational level, and no statistical significant difference as for , special education teachers and the variable of training courses. Finally we made some procedural recommendations ,most importantly, helping and encouraging special education teachers to join training and higher education specially in their field of work. We observed a lack of studies specially higher ones and recommendations for future research.
مذكرة ماستر علوم التربية تخصص تربية خاصة
Keywords: الضغوط النفسية; Stress psychologique; Psychological stress